Rooperol, an inhibitor of cytokine synthesis, decreases the respiratory burst in human and rat leukocytes and macrophages - A. Guzdek; B. Turyna; A. C. Allison; K. Sladek; A. Koj (Mediators of Inflammation)
Luminol-enhanced chemiluminescence was measured in fresh whole human blood, or human neutrophils isolated from heparinized blood, human alveolar macrophages and rat alveolar macrophages stimulated with bacterial endotoxin (LPS). Tetraacetate esters of rooperol, a dicatechol showing anticytokine activity, added to cells simultaneously with LPS inhibited the respiratory burst. The effective concentrations of rooperol were in the range of 1-10 μM depending on cell type and corresponded well with inhibition of nitric oxide production by rat alveolar macrophages. Thus rooperol may reduce some effects of excessive phagocytic activity and inflammatory reaction but by quenching free radicals production may also diminish the resistance to bacterial infections.